Islamophobia, Indian Media, and Covid-19 Pandemic: A Critical Discourse Analysis - Andi Farid Baharuddin; A Zamakhsyari Baharuddin (Islam Realitas: Journal of Islamic and Social Studies, 2022)
This research is designed to demonstrate (1) how the Indian media attempts to construct the Islamophobia issue during the Covid-19 pandemic (particularly in the earlier March-April, 2020) and (2) how the Indian news media use social media, such as Instagram and Twitter, to claim that Muslims were the disseminators of the virus to the majority of Indian population. In collecting and analyzing data, the researchers use the descriptive qualitative methodology as the scientific research procedure. There are three collected data classified in this research i.e., the primary data, the secondary data, and the supporting data. Furthermore, in analyzing the data, the researchers appled the critical discourse analysis (CDA) as the linguistics theory to study the Islamophobia discourse on the news media. Finally, the research result shows that (1) most of the Indian mainstream media not only spread Islamophobia but also justify and hegemonize Muslims as Corona virus disseminators , and (2) these news media eventually influenced hate speech memes and racial statements posted by Indian netizens/Buzzers on social media that accuse Muslim minority as the disseminator of the Corona virus. Penelitian ini dirancang untuk menunjukkan (1) bagaimana upaya media India dalam mengkonstruksi wacana Islamofobia kepada warga sipil selama pandemi Covid 19 (khususnya pada awal Maret-April 2020) dan (2) bagaimana berita media India memiliki berimplikasi pada penggunaan media sosial seperti Instagram dan Twitter, yang mengklaim minoritas Muslim sebagai penyebar virus Corona terhadap mayoritas penduduk India. Untuk mengumpulkan dan menganalisis data penelitian, peneliti menggunakan metodologi deskriptif kualitatif sebagai prosedur penelitian ilmiah. Data yang terkumpul diklasifikasikan menjadi tiga data yaitu data primer, data sekunder, dan data pendukung. Selanjutnya, dalam menganalisis data, peneliti menerapkan analisis wacana kritis (CDA) sebagai teori linguistik untuk memahami dan mempelajari wacana Islamofobia berdasarkan berita media. Akhirnya, hasil penelitian menunjukkan fakta yang sebenarnya bahwa (1) sebagian besar media utama India tidak hanya mengkonstruksi wacana Islamofobia namun juga membenarkan dan menghegemoni bahwa masyarakat muslim merupakan penyebar virus Corona (2) berita media ini pada akhirnya berimplikasi pada meme ujaran kebencian dan pernyataan rasial yang diposting oleh netizen/Buzzers India di media sosial yang menuduh minoritas Muslim sebagai penyebar virus Corona.